IMDIS. A Teaching Tool for Air Pollution Dispersion Modelling - Salcedo, Romualdo (De Gruyter, 2020)
This book intends to give both course instructors and undergraduate students a tool to follow-up on a better comprehension of APM with the aid of hands-on user-friendly software, highlighting the main advantages of using Gaussian Dispersion as the main drive to teach this subject. The author believes that the disadvantages of Gaussian modeling are by far surpassed by the advantages, at least at an entry level to the subject.